THE ECONOMICS OF PRODUCTION, UTILIZATION AND MARKETING OF COCONUT FLOUR FROM COCONUT MILK RESIDUE - Divina D. Bawalan (International Coconut Community Journal, 2000)
Recent developments in the world market such as the General Agreements on Tariff and Trade (GATT), quality management systems (ISO 9000), environmental management systems (ISO 14000), etc. force industries to re-evaluate their existing products and manufacturing systems and procedures. Suddenly, being ISO certified has become both the tool and the badge for the goal of global competitiveness. It is a well known fact that to be globally competitive and to be ISO certified, one must be able to produce quality products at the least cost and with the least waste of materials. This can be done by producing more value-added products from a single raw material with the least inputs.